Roles of Waqf in Supporting Economy Recovery Post Covid-19 Pandemic - Iskandar, Iskandar; Kurlillah, Anis; Munadiati, Munadiati (ZISWAF, 2023)
The Covid-19 pandemic that has occurred since the end of 2019 has caused many problems in human life. The problems are not only in the health sector but also in the economy, education, and social welfare. This paper aims to identify the roles of waqf as an instrument that can be an alternative to overcome those economic and social problems. This study employed qualitative research designed using document analysis of journal articles, books, reports, online resources, policy documents, and related published material. Waqf has demonstrated its significant role in addressing the challenges posed by the COVID-19 pandemic, providing solutions in various sectors such as healthcare, social welfare, education, and economic recovery. Waqf has played an important role as a provider of relief and eased the burden on communities affected by the pandemic. In addition, another role that needs to be played by waqf manager (nazir) is to build collaboration between waqf institutions, governments, and international organizations are essential to ensure the sustainable utilization of waqf assets for the benefit of society. This study could shed light on how waqf institutions could plan, strategize, and implement appropriate measures to assist those affected by the pandemic in the future.